Emotion regulation and well-being - Nyklíček, Ivan; Vingerhoets, A. J. J. M.; Zeelenberg, Marcel (Springer e., 2011)
"Emotion is a basic phenomenon of human functioning, most of the time having an adaptive value enhancing our effectiveness in pursuing our goals in the broadest sense. Regulation of these emotions, however, is essential for adaptive functioning, and suboptimal or dysfunctional emotion regulation may even be counterproductive and result in adverse consequences, including a poor well-being and ill health. This volume provides a state-of-the art overview of issues related to the association between emotion regulation and both mental and physical well-being. It covers various areas of research highly relevant to both researchers in the field and clinicians working with emotion regulation issues in their practice."--Publisher's descripti